2020
DOI: 10.1111/vox.12984
|View full text |Cite
|
Sign up to set email alerts
|

Civilian prehospital transfusion – experiences from a French region

Abstract: Background and objectives Haemorrhagic shock is a leading cause of avoidable mortality in prehospital care. For several years, our centre has followed a procedure of transfusing two units of packed red blood cells outside the hospital. Our study’s aim was twofold: describe the patient characteristics of those receiving prehospital blood transfusions and analyse risk factors for the 7‐day mortality rate. Materials and methods We performed a monocentric retrospective observational study. Demographic and physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Nearly half of the patients receiving PHBT were non-traumatic, with the most common reason being gastrointestinal hemorrhage. Previous studies have reported the non-traumatic group being anywhere from 22-68% of the patients receiving PHBT and gastrointestinal hemorrhage being the most common reason [10,12,14,15,16]. The patient characteristics observed in our study closely echo previous research.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nearly half of the patients receiving PHBT were non-traumatic, with the most common reason being gastrointestinal hemorrhage. Previous studies have reported the non-traumatic group being anywhere from 22-68% of the patients receiving PHBT and gastrointestinal hemorrhage being the most common reason [10,12,14,15,16]. The patient characteristics observed in our study closely echo previous research.…”
Section: Discussionsupporting
confidence: 87%
“…The patient characteristics observed in our study closely echo previous research. Overall, the non-traumatic group consisted of older patients and in deeper anemia compared to the traumatic group [12,10,15]. The traumatic group consisted of younger, mostly males suffering blunt traumas [2,12,17].…”
Section: Discussionmentioning
confidence: 99%
“…The patient characteristics observed in our study closely echo previous research. Overall, the non-traumatic group consisted of older patients and in deeper anemia compared to the traumatic group [ 10 , 12 , 15 ]. The traumatic group consisted of younger, mostly males suffering blunt traumas [ 2 , 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The objective of these scores is to identify major trauma patients requiring transfusion at an early stage in order to anticipate the amount of labile blood products needing to be ordered by the receiving trauma centre [8]. Although the capability for pre‐hospital blood transfusion is being implemented in some areas, it is not yet widely accepted as a standard practice [9]. Effective pre‐hospital management and triage of these major trauma patients to dedicated trauma centres reduce their mortality by 25% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the capability for pre-hospital blood transfusion is being implemented in some areas, it is not yet widely accepted as a standard practice [9]. Effective pre-hospital management and triage of these major trauma patients to dedicated trauma centres reduce their mortality by 25% [10].…”
Section: Introductionmentioning
confidence: 99%